Simulation of Retrofitted Unreinforced Concrete Masonry Unit Walls under Blast Loading. Issue 1 (March 2013) - Aghdamy, Sanam; Wu, Chengqing; Griffith, Michael
This paper describes an investigation into the effectiveness of using spray-on nano-particle reinforced polymer and aluminium foam as new types of retrofit material to prevent the breaching and collapse of unreinforced concrete masonry walls subjected to blast over a whole range of dynamic and impulsive regimes. Material models from the LS-DYNA material library were used to model the behaviors of each of the materials and its interface for retrofitted and unretrofitted masonry walls. Available test data were used to validate the numerical models. Using the validated LS-DYNA numerical models, the pressure-impulse diagrams for retrofitted concrete masonry walls were constructed. The efficiency of using these retrofits to strengthen the unreinforced concrete masonry unit (CMU) walls under various pressures and impulses was investigated using pressure-impulse diagrams. Comparisons were made to find the most efficient retrofits for masonry walls against blasts.